Can athletes jump high while landing safely? - Fox, A. S. (SportRxiv, 2019)
Rapid jump-landing is an important performance determinant across sports. While the jump is important for performance, the preceding landing may expose athletes to anterior cruciate ligament (ACL) injury. `Safe` landing techniques are promoted to minimise injury risk, however it is important that these are not detrimental to subsequent jumping performance. This study determined whether there is a relationship between biomechanical factors associated with ACL loading or injury risk and jump performance during a bilateral drop vertical jump. Thirty-two female sub-elite netball players had three-dimensional (3D) data recorded from a bilateral drop vertical jump task. 3D hip, knee and ankle joint rotations, 3D knee joint moments, and 3D ground reaction forces (GRFs) were extracted from the landing phase of the task. Jump height, ground contact time and peak power output were extracted from the jumping phase of the task. One-dimensional statistical parametric mapping (p < 0.0011) was used to investigate the relationship between the landing and jumping phases. Greater knee internal rotation moments and higher GRFs during landing were associated with reduced jump height. Greater hip and knee flexion, reduced hip internal rotation and knee abduction, and a more dorsiflexed/less plantarflexed ankle position at initial contact during landing were associated with longer ground contact times. Certain biomechanical factors commonly targeted within ACL injury prevention programs were associated with both poorer and better jump performance. The links between landing technique and jumping performance suggest jump performance training should be considered in parallel with landing injury prevention programs.